Larvicidal Activities and Synergistic Effects of Essential Oils against Anopheles funestus and Culex quinquefasciatus (Diptera: Culicidae) from Kisumu, Kenya. (8th March 2022) - Wangrawa, Dimitri W.; Kosgei, Jackline; Machani, Maxwell; Opala, James; Agumba, Silas; Yaméogo, Felix; Borovsky, Dov; Ochomo, Eric
Abstract : Rapid development of resistance in vector mosquitoes to synthetic insecticides is a major challenge for malaria control. The use of plant-derived essential oils (EOs) is an attractive strategy in controlling mosquito populations because they are environmentally safe and may have a lower chance of developing resistance. This study assessed the larvicidal activities of EOs from Lantana camara, Lippia multiflora, Lippia chevalieri, and Cymbopogon schoenanthus against Anopheles funestus and Culex quinquefasciatus . The 3 rd –4 th instar larvae were tested using a World Health Organization (WHO)-modified protocol to evaluate larval mortality 24 h after exposure to EOs and their binary combinations. Culex quinquefasciatus larvae were more susceptible to EOs than An. funestus larvae. For Cx. quinquefasciatus, the lethal concentrations at 50% mortality (LC50 s) of EOs from C. schoenanthus, L. multiflora, L. camara, and L. chevalieri were 23.32, 27.24, 38.54, and 54.11 ppm, respectively; whereas for An. funestus, the EO LC50 s were 120.5, 67.5, 49.21, and 105.74 ppm, respectively. Synergistic effects were observed using EOs from C. schoenanthus  +  L. multiflora (LC50  = 44.05 ppm) on An. funestus, while L. camara  +  L. chevalieri (LC50  = 33.16 ppm), L. chevalieri  +  C. schoenanthus (LC50  = 12.08 ppm), and L. multiflora  +  L. chevalieri (LC50  = 20.61 ppm) were synergistic for Cx. quinquefasciatus . These results indicate the potential of EOs derived from local plants and their binary combinations as botanical larvicides. The EOs could be used as future ecofriendly agents to control these vectors.